2015
DOI: 10.1002/adsc.201400870
|View full text |Cite
|
Sign up to set email alerts
|

Silver Hexafluoroantimonate‐Catalyzed Direct α‐Alkylation of Unactivated Ketones

Abstract: A practically simple and direct a-alkylation of unactivated ketones using benzylic alcohols has been achieved. The in situ formed acetals are the key for the success of the reaction. The catalyst, silver hexafluoroantimonate(V) (AgSbF 6 ) provides double activation by converting the ketone into an enol ether via acetal and generation of carbocationic center at the benzylic position of the benzylic alcohol. The alcohols include benzylic propargyl alcohols, cinnamyl alcohols, and diarylmethanols.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(16 citation statements)
references
References 120 publications
0
15
0
1
Order By: Relevance
“…[37] In this iridium-catalyzed interrupted process both the enone 7 and methoxy adduct 8 were not isolated but reacted in situ with an external nucleophile and extra base.I tw as found that treatment of the reaction mixture with the metal-scavenging resin (SiliaMetS DMT) [38] was beneficial to the subsequent reaction to produce the products 9.A gSbF 6 was reported to catalyze the direct a-alkylation of unactivated ketones by benzylic alcohols. [39] With [{IrCl(cod)} 2 ]/PPh 3 as the catalyst in the presence of tBuOK, primary alcohols reacted with tert-butyl acetate in tBuOH at 100 8 8Ct of orm the a-alkylated esters 10 in up to 89 %yield (Scheme 6). [40] With 1,9-nonanediol as the alkylating agent the reaction gave di-tert-butyl tridecanoate (11), which can be applied in the synthesis of afragrant compound, ethylene brassylate (Musk T).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[37] In this iridium-catalyzed interrupted process both the enone 7 and methoxy adduct 8 were not isolated but reacted in situ with an external nucleophile and extra base.I tw as found that treatment of the reaction mixture with the metal-scavenging resin (SiliaMetS DMT) [38] was beneficial to the subsequent reaction to produce the products 9.A gSbF 6 was reported to catalyze the direct a-alkylation of unactivated ketones by benzylic alcohols. [39] With [{IrCl(cod)} 2 ]/PPh 3 as the catalyst in the presence of tBuOK, primary alcohols reacted with tert-butyl acetate in tBuOH at 100 8 8Ct of orm the a-alkylated esters 10 in up to 89 %yield (Scheme 6). [40] With 1,9-nonanediol as the alkylating agent the reaction gave di-tert-butyl tridecanoate (11), which can be applied in the synthesis of afragrant compound, ethylene brassylate (Musk T).…”
Section: Methodsmentioning
confidence: 99%
“…Fore xample,w hen using (oaminophenyl)methanol as the primary alcohol substituted quinolines (66)w ere obtained [Eq. (39)]. [114] These reactions also proceeded either under neat conditions at 130 8 8Ci nt he presence of 100 mol %NaOH and anitrogen atmosphere,or in refluxing toluene by means of 100 mol %KOH under an air atmosphere.…”
Section: Transition-metal-free Reactionsmentioning
confidence: 99%
“…While working on the silver‐catalyzed direct α‐alkylation of unactivated ketones using propargyl alcohols, the tertiary propargyl alcohols did not undergo α‐alkylation at room temperature . Instead, they were converted into α,β‐unsaturated enones via a Meyer‐Schuster rearrangement.…”
Section: Resultsmentioning
confidence: 99%
“…Hydration products 1a‐H and 1a‐H′ were inactive toward allylic alcohol 3c in the presence of Ph 3 PAuCl/AgOTf under similar conditions. According to a recent report, a mixture of trimethoxymethane and AgOTf catalyst enabled the conversion of unactivated ketones to enol ethers that undergo subsequent α‐alkylations with propargylic alcohols to give propylation products . That no reaction occurred for these reactants is not surprising.…”
Section: Methodsmentioning
confidence: 99%